2005
DOI: 10.4040/jkan.2005.35.6.979
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of a Computerized Nursing Process Program for Orthopedic Surgery Inpatients: NANDA, NOC, and NIC Linkages

Abstract: It is expected that this program will help nurses perform their nursing processes more efficiently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 3 publications
0
15
0
2
Order By: Relevance
“…The most frequently selected nursing diagnosis was acute pain; this result is consistent with previous research conducted with nursing students (Lee, ; Lee et al., ; Min, ). In addition, nurses working in the orthopedics unit (Kim, ), medical‐surgical unit (Ko, ; Park, ), general surgical unit (Lee, ), and the obstetrics and gynecological unit (Kim, ) selected acute pain as the most prevalent nursing diagnosis for patients under their care, regardless of clinical setting. Nurses in other countries such as Australia, Sweden, and United States reported that pain was the most frequently used nursing diagnosis (Ehrenberg & Ehnfors, ; King, Chard, & Elliot, ; O'Connor, Hameister, & Kershaw, ) in hospitals and nursing homes.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently selected nursing diagnosis was acute pain; this result is consistent with previous research conducted with nursing students (Lee, ; Lee et al., ; Min, ). In addition, nurses working in the orthopedics unit (Kim, ), medical‐surgical unit (Ko, ; Park, ), general surgical unit (Lee, ), and the obstetrics and gynecological unit (Kim, ) selected acute pain as the most prevalent nursing diagnosis for patients under their care, regardless of clinical setting. Nurses in other countries such as Australia, Sweden, and United States reported that pain was the most frequently used nursing diagnosis (Ehrenberg & Ehnfors, ; King, Chard, & Elliot, ; O'Connor, Hameister, & Kershaw, ) in hospitals and nursing homes.…”
Section: Discussionmentioning
confidence: 99%
“…These benefits of linkages, in particular the linkages among NANDA, the NIC, and the NOC (NNN), have been tested in many other studies and have been presented in the Biennial Conference of the NANDA, NIC, and NOC Alliance and in diverse publications. Meanwhile, in Korea, only a few researchers have explored NNN linkages in general hospitals, [57][58][59] with no emphasis on home care settings.…”
Section: Discussionmentioning
confidence: 99%
“…on NANDA, NIC, and NOC (NNN) linkages and several Korean studies 25,[57][58][59]. These linkages were reviewed by home care nurses employed by a hospital.…”
mentioning
confidence: 99%
“…간호사의 근무지 특성과 학습 환경에 따라 차이가 있는 것으로 나 타났으며 (Kim, 2005;Song, 2010), 간호사의 개인적 특성이 기초 의학 용어를 활용하는 데 영향을 미칠 수 있음이 제시되었다 (Hwang, Kim, & Wang, 2011). …”
Section: 한편 임상 간호 실무에서 기초 의학용어를 활용하는 데 있어서unclassified